Carbon dioxide sequestration: influence of porous media on hydrate formation kinetics - Bhattacharjee, Gaurav; Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (ACS Sustainable Chemistry & Engineering, 2015)
In the present study, CO, sequestration by hydrate formation in porous sediments has been discussed. Two siliceous materials with high porosities, pumice and fire hardened red clay (FHRC), have been used as packing materials in a fixed bed setup to study hydrate formation kinetics. The results obtained using the aforementioned materials were compared with those obtained using silica sand and quartz. Carbon dioxide hydrate formation kinetics was studied at 3.0 MPa pressure and 274 K temperature. Two different types of experiments were conducted: (a) using a constant volume of water and (b) maintaining a constant bed height. These experiments were conducted using the different porous media individually as packing materials. It was observed that pumice as the porous medium showed better hydrate formation kinetics resulting in 46 mol % water to hydrate conversion in 5 h. Moreover, kinetics was enhanced with decrease in the bed height of pumice; this suggests that at field scale adaptation of CO, sequestration in geological formations, mass transfer limitations would be significant. The effects of particle size on hydrate formation kinetics were also investigated. It was observed that hydrate formation kinetics was enhanced with decrease in the particle size fraction.
Keywords: Bed height; Gas hydrate; gas uptake; Geological sequestration; Particle size

Role of surfactants in promoting gas hydrate formation - Kumar, Asheesh; Bhattacharjee, Gaurav; Kulkarni, B. D.; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2015)
Gas hydrates have been proposed as a potential technology for a number of applications, such as separation of gas mixtures, CO2 capture, transportation, and sequestration, methane storage and transport, and seawater desalination. Most of these applications will benefit from reduced induction time of hydrate nucleation, enhanced hydrate growth rate, and maximum water-to-hydrate conversion. The addition of surfactants to the gas-water system serves this purpose in a very effective manner. This review focuses on different surfactants that were utilized for gas hydrate formation studies; insights have been provided on the possible mechanisms of action through which these surfactants affect hydrate formation kinetics. A thorough analysis of the existing literature on surfactants suggests that enhanced rate of hydrate nucleation and growth kinetics may not be directly linked to micelle formation. Conversely, reduced surface tension in the presence of surfactants not only enhances the mass transfer but also changes the morphology of hydrate formation, which in turn enhances gas-water interactions for faster hydrate growth rate.

Effect of different fixed bed media on the performance of sodium dodecyl sulfate for hydrate based CO2 capture - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Kumar, Pushpendra; Balomajumder, Chandrajit (Materials & Design, 2016)
Sodium Dodecyl Sulfate (SDS) is used as a kinetic promoter in gas hydrate formation. In this work, the performance of SDS for carbon dioxide gas hydrate formation in two different fixed bed media: silica sand and zeolite (5A and 13X) has been evaluated. The concentration of SDS was fixed at 0.5 wt%. The experiments were carried out in batch mode with the initial pressure fixed at 3.0 MPa, and the temperature kept constant at 274.65 K. The results showed that hydrate of carbon dioxide with fixed bed of silica sand was significantly promoted by the addition of SDS as compared to the other fixed bed medium used in this study: zeolite 13X. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide; Fixed bed media; Hydrate formation; Kinetic promoter; Silica sand; Zeolite 5A and 13X

Effect of the amino acid L-histidine on methane hydrate growth kinetics - Bhattacharjee, Gaurav; Choudhary, Nilesh; Kumar, Asheesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Natural Gas Science and Engineering, 2016)
In the present study, the effect of a polar amino acid, L-histidine on methane hydrate growth kinetics has been investigated. Methane hydrate formation experiments were carried out in a stirred tank reactor setup at pressure and temperature conditions of 274.15 K and 5.0 MPa respectively. Two different concentrations (0.1 and 1 wt %) of L-histidine were studied. Hydrate growth through molecular dynamic (MD) simulation was also studied; pressure and temperature conditions for the simulations were set at 10.0 MPa and 270.0 K, while the concentration of L-histidine was kept fixed at 0.94 wt %. Hydrate formation runs using MD simulation were carried out with optimal concentration of methane in water. The presence of L-histidine in the system was found to significantly enhance methane hydrate growth kinetics as compared to pure water for both experimental and MD simulation runs. Final gas consumption with 1 wt % L-histidine was found to be comparable to that with 1 wt % SDS, the most commonly used additive for hydrate promotion studies. L-histidine is a benign additive which offers considerable enhancement in methane hydrate formation kinetics and can be utilized for various hydrate based technologies such as methane storage and transport. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Crystal growth; Gas hydrate; kinetics; Molecular dynamic simulation

Impact of H2S impurity on carbon dioxide hydrate formation kinetics in fixed bed arrangements - Kumar, Asheesh; Sakpal, Tushar; Bhattacharjee, Gaurav; Kumar, Anupam; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2016)
In the present work, a combination of silica sand and metallic sheets as a fixed bed media was used for carbon dioxide hydrate formation studies. Two metallic sheets, aluminum and brass, were incorporated into the fixed bed of silica sand to enhance heat transfer properties of the bed. The results obtained from this arrangement of metal sheets were compared with those obtained with a pure silica sand system. Both brass and aluminum systems were found to be good candidates to enhance gas hydrate formation kinetics compared to simply a sand system. Production of fuel gas from coal often contains a toxic gas, hydrogen sulfide (H2S). For the first time, the effect of H2S on the formation kinetics of CO2 + H-2 + H2S hydrates has been studied. It was observed that the presence of H2S does not affect the hydrate formation kinetics and total gas uptake in the presence of H2S is either as good as CO2 + H-2 hydrate or better. However, H2S impurity in the fuel gas mixture shows a corrosive effect on silica sand media.

Biosurfactant surfactin as a kinetic promoter for methane hydrate formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Pradhan, Darshan; Naik, Rajesh; Zare, Kirti; Mawlankar, Rahul R.; Dastager, Syed Gulam; Kushwaha, Omkar Singh; Kumar, Rajnish (Energy Procedia, 2017)
In the present study, the effect of the biosurfactant Surfactin on methane hydrate formation kinetics was studied. Initially, several marine derived species were screened for the presence of Surfactin. The polymerase chain reaction technique was used as the preliminary screening step for Surfactin which was then followed up by a couple of different assays to provide conclusive evidence of the same. Based on these tests, the D-9 bacterial strain was identified as a producer of Surfactin. Once the presence of Surfactin had been proven, its effect on methane hydrate formation kinetics was investigated upon by carrying out hydrate formation experiments in a stirred tank reactor. The cell free supernatant containing Surfactin was itself used as the hydrate forming solution without any further processing. It was found that the presence of Surfactin in the system greatly enhances hydrate formation kinetics as compared to pure water. In fact the kinetics in presence of Surfactin also surpassed that obtained with 1 wt% SDS, the most commonly used synthetic kinetic hydrate promoter. This basic study can pave the way for more sophisticated research on the use of biosurfactants as kinetic promoters with a view on rapid methane hydrate formation kinetics for applications such as methane separation, storage and transport.

Effects of micellization on growth kinetics of methane hydrate - Bhattacharjee, Gaurav; Kushwaha, Omkar Singh; Kumar, Asheesh; Khan, Muzammil Yusuf; Patel, Jay Narayan; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2017)
Surfactants are Specific functional materials, that form various types of self-assemblies and affect local water ordering alongside solution properties. Such surface active agents are used extensively in gas hydrate based applications as kinetic hydrate promoters. To understand the effect of surfactant micelles on hydrate formation kinetics, a novel surfactant system capable of producing micelles at hydrate forming temperature was developed. The presence of surfactant micelles in this new system (a combination of anionic surfactant SDS and zwitterionic surfactant CAPB) was determined through DLS measurements. Pure methane and a coal bed methane mixture were individually used to assess the efficacy of the surfactant mixture for hydrate formation. This study conclusively proves for the first time that the presence of surfactant micelles enhances hydrate formation kinetics. The findings reported here can contribute significantly toward improving the utility of surfactants in gas hydrate based technological applications such as gas separation and methane storage.

Molecular dynamics simulation and experimental study on the growth of methane hydrate in presence of methanol and sodium chloride - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Energy Procedia, 2017)
The plugging of processing and transportation lines by gas hydrate formation is a challenging problem for safe exploitation of oil and gas. The existence of water soluble third component (like methanol and sodium chloride) in the aqueous phase influence the gas hydrate formation thermodynamically also possibly affects the kinetics of hydrate growth. Inorganic salt and organic molecule (alcohols) at high concentration in the aqueous phase have been used as thermodynamic inhibitors to effectively prevent the hydrate formation. This study utilizes molecular dynamics as well as an experimental method to investigate the mechanism of the hydrate formation and the effect of additives. The MD simulation showed that at moderate temperature and pressure, a low concentration (1 wt %) of methanol and NaCl enhances methane hydrate growth kinetics. Significant numbers of methanol molecules were observed inside the gas hydrate cages whereas Na⁺/Cl⁻ ions leach out during hydrate formation.

Kinetic promotion of methane hydrate formation by combining anionic and silicone surfactants: scalability promise of methane storage due to prevention of foam formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Kushwaha, Omkar S.; Kumar, Rajnish (Journal of Chemical Thermodynamics, 2018)
Methane storage in its solid hydrate form has recently come up as a rather attractive and low risk option for large scale storage of the gas owing to its mild storage conditions, high gas retention capacity and benign (non-explosive) character. However, it has its fair share of limitations with the slow rate of hydrate formation being one of the most prominent. The addition of surfactants like Sodium dodecyl sulfate (SDS) to the hydrate forming system significantly speeds up the process of methane hydrate formation but the large amount of foam generated by these surfactants during the process of hydrate formation and dissociation stands as a major roadblock towards the scaling up of the technology. In the current work, a small amount of a silicon based surfactant has been proposed to be used as antifoam in conjunction with an anionic surfactant SDS to eliminate the foam generation while at the same time promote the kinetics of methane hydrate formation. The idea is simple, cost effective and can be a potential game-changer in the quest to develop a commercially scalable hydrate based methane storage technology. (C) 2017 Elsevier Ltd.
Keywords: Antifoam; Gas hydrate; kinetics; Methane storage; scale-up; Silicone surfactant

Methane recovery from marine gas hydrates: a bench scale study in presence of low dosage benign additives - Bhattacharjee, Gaurav; Choudhary, Nilesh; Barmecha, Vivek; Kushwaha, Omkar S.; Pande, Nawal K.; Chugh, Parivesh; Roy, Sudip; Kumar, Rajnish (Applied Energy, 2019)
De-pressurization is one approach which has been found to be economically feasible for methane recovery from marine hydrates. Hydrate dissociation being an endothermic process suggests that de-pressurization alone would not be sufficient and some additional stimulation would be required for sustained production from one such reservoir. Thermal stimulation may overcome the challenge posed by the endothermic dissociation process; however, economically it may not be ideal. A possible way out is to use thermal stimulation, but at relatively low temperatures as compared to conventional practice. This would be economical and can be accomplished in the presence of small doses of additives mixed in with the water stream used for thermal stimulation. In the present study, a number of benign additives were identified which when used in low concentrations enhance the kinetics of methane hydrate dissociation compared to pure water. Additives were first shortlisted from a wide potential pool using quantum mechanical calculations. These additives were later tested for their efficacy in stirred tank reactor to quickly identify the best additives for the job and few selected additives were then studied in a larger bench scale setup (fixed bed configuration) where they were injected in the form of an additive-water stream to dissociate already formed hydrates. Factors such as toxicity of the additive, fluidity of additive-water stream, foam formation on mixing of additive with water, etc. were also taken into account. An energy and efficiency analysis revealed that reported additives enhance the energy ratio and thermal efficiency of the process as compared to pure water stimulation.
Keywords: Bench scale; kinetics; Marine hydrate; methane hydrate; Methane recovery; Natural gas hydrate; Process

Macro and molecular level insights on gas hydrate growth in the presence of hofmeister salts - Choudhary, Nilesh; Kushwaha, Omkar Singh; Bhattacharjee, Gaurav; Chakrabarty, Suman; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2020)
The effect of few monovalent salts (NaCl, NH4Cl, and GdmCl) as additives, according to the Hofrneister series on the growth of methane gas hydrates, has been studied using experiments as well as molecular dynamics (MD) simulation. Further, the Hofmeister effects on hydrate crystallization have been correlated with the methanol as an additive, which is a known thermodynamic hydrate inhibitor for hydrate growth. One of the previous studies (discussed later in this article) available in the literature concludes that methane hydrate formation from ice might show enhanced kinetics in the presence of salts; this behavior is contrary to the general usage of such salts as hydrate inhibitors. This conclusion may not necessarily be true for experiments done with liquid water, and therefore, this work explores the behavior of these salts in a lab-scale setup. In addition, current work reports detailed MD simulation studies to gain insight into the mechanism of hydrate formation in the presence of Hofmeister series salts at two different concentrations of 1 and 10 wt % in water and compare the results with hydrate formation in the methanol-water system. Our study suggests that the presence of these additives at low concentrations (1 wt %) does enhance the hydrate growth kinetics. However, at higher concentrations (10 wt %), inhibition by these additives persisted, and prolonged nucleation, as well as retarded growth, was observed.

Hydrate-based carbon capture process: assessment of various packed bed systems for boosted kinetics of hydrate formation - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Balomajumder, Chandrajit; Kumar, Pushpendra (Journal of Energy Resources Technology-Transactions of the ASME, 2021)
The case for developing novel technologies for carbon dioxide (CO2) capture is fast gaining traction owing to increasing levels of anthropogenic CO2 being emitted into the atmosphere. Here, we have studied the hydrate-based carbon dioxide capture and separation process from a fundamental viewpoint by exploring the use of various packed bed media to enhance the kinetics of hydrate formation using pure CO2 as the hydrate former. We established the fixed bed reactor (FBR) configuration as a superior option over the commonly used stirred tank reactor (STR) setups typically used for hydrate formation studies by showing enhanced hydrate formation kinetics using the former. For the various packing material studied, we have observed silica gel with 100 nm pore size to return the best kinetic performance, corresponding to a water to hydrate conversion of 28 mol% for 3 h of hydrate growth. The fundamental results obtained in the present study set up a solid foundation for follow-up works with a more applied perspective and should be of interest to researchers working in the carbon dioxide capture and storage and gas hydrate fields alike.
Keywords: air emissions from fossil fuel combustion; Carbon dioxide capture; combustion of waste; Fixed bed reactor; fuel combustion; Gas hydrate; hydrates; kinetics; Silica gel